Tolerance to nitroglycerin through proteasomal down‐regulation of aldehyde dehydrogenase‐2 in a genetic mouse model of ascorbate deficiency. (25th March 2013) - Wölkart, G; Beretta, M; Wenzl, MV; Stessel, H; Schmidt, K; Maeda, N; Mayer, B; Schrammel, A
<x xml:space="preserve">Abstract</x> Background and Purpose L‐gulonolactone oxidase‐deficient (Gulo(‐/‐)) mice were used to study the effects of ascorbate deficiency on aortic relaxation by nitroglycerin (GTN) with focus on changes in the expression and activity of vascular aldehyde dehydrogenase‐2 (ALDH2), which catalyses GTN bioactivation. Experimental Approach Ascorbate deficiency was induced in Gulo(‐/‐) mice by ascorbate deprivation for 4 weeks. Some of the animals were concomitantly treated with the proteasome inhibitor bortezomib and effects compared with ascorbate‐supplemented Gulo(‐/‐), untreated or nitrate‐tolerant wild‐type mice. Aortic relaxation of the experimental groups to GTN, ACh and a NO donor was studied. Changes in mRNA and protein expression of vascular ALDH2 were quantified by qPCR and immunoblotting, respectively, and aortic GTN denitration rates determined. Key Results Like GTN treatment, ascorbate deprivation induced vascular tolerance to GTN that was associated with markedly decreased rates of GTN denitration. Ascorbate deficiency did not affect ALDH2 mRNA levels, but reduced ALDH2 protein expression and the total amount of ubiquitinated proteins to about 40% of wild‐type controls. These effects were largely prevented by ascorbate supplementation or treating Gulo(‐/‐) mice with the 26S proteasome inhibitor bortezomib. Conclusions and Implications Our data indicate that ascorbate deficiency results in vascular tolerance to GTN via proteasomal degradation of ALDH2. The results support the view that impaired ALDH2‐catalysed metabolism of GTN contributes significantly to the development of vascular nitrate tolerance and reveal a hitherto unrecognized protective effect of ascorbate in the vasculature.